VALUASI EKONOMI NILAI GUNA TIDAK LANGSUNG KAWASAN MANGROVE DI KELURAHAN SETAPUK BESAR KOTA SINGKAWANG - Nandu, Iphon; Roslinda, Emi; Hardiansyah, Gusti (Universitas Tanjungpura, 2019)
This research to determine the indirect use value of coastal protection by planting mangroves in Setapuk Besar Village and comparing the benefits between the development of coastal protection in biological and physical. research was carried out from July-August 2018. this study used descriptive quantitative method. Analyze the data using the replacement cost method. Interview was carried out only with key respondents who as acted the chairman of the SPM (Surya Perdana Mandiri) association in Setapuk Besar. The results showed that total costs incurred are based on planting, protection, work wages and inventory activities of Rp. 270.182.000 there was 4 (four) financing according to the object of expenditure in the mangrove return activities (Enrichment). The cost of returning mangroves is much cheaper than the cost of making breakwaters other than that the benefits of mangroves are far more than building protection with Breakwater.Keyword: Economic valuation, Mangrove, replacement cost